REVITALISASI PASAR TRADISIONAL (STUDI TENTANG PERSEPSI PEDAGANG DI PASAR RUMBAI KOTA PEKANBARU - Swendy Sandina; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Revitalization Rumbai Market aims to make people comfortable to stalls in a comfortable and traders sell and earn huge profits. But the reality does not make merchants happy, because the price is expensive stalls which according to traders does not help increase their income. perceptions of traders to revitalize Rumbai Market less well, especially traders who already occupy a stall with a strategic position. after the market was completed and occupied, hoping for a big profit, but actually lose money so that the perception of traders towards the construction of kiosks remain unfavorable. so that eventually some traders left the stall, above phenomena can be formulated several research problem is: How do the characteristics of traders who occupy the stall and How the perception of traders to development Rumbai Market stalls. Traders stalls characteristics include: Traders largely have stalls in the Market Rumbai aged 30 years and above, are the largest ethnic group Minangkabau ethnic group, traders are earning more than Rp 3,000,000.00 per month is only 10 percent or 2 respondents, while most revenue is Rp 1.500.000,00 - Rp 3,000,000.00 by the number of family members as much as 3 to 4 people. Perception on Development considers that the Dealer Store Market development Tassel, initially will bring an improvement in its trading business, but in fact after the construction of stalls in the Market Rumbai finished, what to expect there to be true and there were not materialize. Perception traders to accessibility in Rumbai market, all respondents (100.0%) say positive, as traders are confident that access to the market Tassel, or otherwise very smooth and no problems. Access to markets can be reached from the District Rumbai Pesisir Pekanbaru City. Most of the respondents (85%) say that the condition of Market Kiosks Rumbai in good condition, results showed that respondents said consumers shopping at his stall lonely in the sense that there are shopping, but few, even sometimes no shopping, visits consumers who shop in stalls respondents only 60 percent of respondents as many as 8 respondents (40%) berpersepsi less well to visit consumers to shop to stall the respondent or it can be said the transaction deserted.Keywords: Revitalization, Perception, Markets